2011
DOI: 10.1159/000331341
|View full text |Cite
|
Sign up to set email alerts
|

Glycerophosphate Is Interchangeable with Inorganic Phosphate in Terms of Safety and Serum Pharmacokinetics

Abstract: Objective: The primary aim of the present investigation was to determine and compare the pharmacokinetic (PK) profiles of inorganic phosphate in serum and urine after intravenous administration of sodium glycerophosphate and inorganic sodium phosphate. Additionally, study product safety profiles were evaluated. Subjects and Methods: In total, 27 healthy, white volunteers (17 male/10 female) were enrolled in this double-blinded, randomized, 2-sequence, crossover study and were assigned to receive an organic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This approach allowed us to obtain a more detailed understanding of the behavior of serum phosphate PKs during test and reference drug administration and also provided the opportunity to verify whether these differences are statistically significant. This additional, out of protocol PK analysis confirmed previous findings of bioequivalence between treatments for the AUC 0-8 , AUC [8][9][10][11][12][13][14][15][16] and AUC 16-36 time fragments. However, the test/reference ratio of the total amount of phosphate in urine collections over 24 h missed the lower bioequivalence boundary, leading to the assumption that urine collections over 24 h are of limited value for the determination of phosphate bioequivalence assessment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This approach allowed us to obtain a more detailed understanding of the behavior of serum phosphate PKs during test and reference drug administration and also provided the opportunity to verify whether these differences are statistically significant. This additional, out of protocol PK analysis confirmed previous findings of bioequivalence between treatments for the AUC 0-8 , AUC [8][9][10][11][12][13][14][15][16] and AUC 16-36 time fragments. However, the test/reference ratio of the total amount of phosphate in urine collections over 24 h missed the lower bioequivalence boundary, leading to the assumption that urine collections over 24 h are of limited value for the determination of phosphate bioequivalence assessment.…”
Section: Discussionsupporting
confidence: 87%
“…In separate experiments, we were able to demonstrate that the serum PK profiles of inorganic phosphate are super-imposable for sodium glycerophosphate and pure inorganic phosphate solution after intravenous administration of equimolar doses to healthy volunteers [9] . The hydrolytic conversion of glycerophosphate to inorganic phosphate is a fast process.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have shown that NaGP has a more favorable serum pharmacokinetic profile and a lower propensity to precipitate with the divalent calcium ion compared with inorganic phosphate. [35][36][37] The purpose of this study was to assess the physical compatibility of calcium chloride with NaGP in PN solutions intended for pediatric patients.…”
Section: Anderson Et Al Physical Compatibility Of Calciummentioning
confidence: 99%
“…The pharmacokinetic profiles of sodium phosphate and sodium glycerophosphate are nearly identical, and the products are both valid options as a phosphate source. 4 In terms of solubility in the presence of calcium, sodium glycerophosphate has been shown to be superior. PN solutions containing glycerophosphate are less likely to precipitate and allow for greater flexibility in calcium and phosphate dosing.…”
mentioning
confidence: 99%